2015
DOI: 10.1016/j.athoracsur.2014.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmission Is Associated With Poor Survival After Esophagectomy for Esophageal Cancer

Abstract: Background Hospital readmissions are costly and associated with inferior patient outcomes. There is limited knowledge related to readmissions following esophagectomy for malignancy. Our aim was to determine the impact of readmission following esophagectomy on survival. Methods This cohort study utilizes Surveillance, Epidemiology, and End Results-Medicare data (2002–2009). Survival, length of stay (LOS), 30-day readmissions and discharge disposition were determined. Multivariate logistic regression models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…Other crucial pay-for-performance program in the U.S [9]. Our results indicate that the incidence of 30-day readmission after an esophagectomy continues to be high at 17.20% and is consistent with previous finds [5,6]. e novel aspect of this study is that it compares the incidence of early readmissions following esophagectomy among centers stratified by annual case volume.…”
Section: Icd-9-cm Code Descriptionsupporting
confidence: 88%
See 1 more Smart Citation
“…Other crucial pay-for-performance program in the U.S [9]. Our results indicate that the incidence of 30-day readmission after an esophagectomy continues to be high at 17.20% and is consistent with previous finds [5,6]. e novel aspect of this study is that it compares the incidence of early readmissions following esophagectomy among centers stratified by annual case volume.…”
Section: Icd-9-cm Code Descriptionsupporting
confidence: 88%
“…Hospital readmissions following esophagectomy range from 12-25% and are associated with decreased patient survival [3,5,6]. However, data regarding risk factors for early (30-day) readmission after esophagectomy have been conflicting.…”
Section: Introduction E Incidence Of Esophageal Adenocarcinoma In Thementioning
confidence: 99%
“…1923 As highlighted by both our study results and those that have been previously published, socioeconomic factors are now starting to be recognized as important preoperative indicators for increased risk of hospital readmission. 9,10,13,23 Although SES factors are non-modifiable in and of themselves, they have been repeatedly linked with poor outcomes, including readmission. 24 Reasons for this finding have included patient preference for hospitalization versus ambulatory care and lack of access to follow-up visits.…”
Section: Commentmentioning
confidence: 57%
“…Given the importance of readmissions as a quality of care metric, readmission rates should be considered in conjunction with other outcomes when determining value. Hospital readmissions following an esophagectomy for esophageal cancer have previously been shown to be a common occurrence, ranging from 5% to 25%, though these reports did not differentiate surgical approaches [25][26][27][28]. In our study, rehospitalization after discharge to home was found to occur frequently.…”
Section: Discussionmentioning
confidence: 99%